(untitled) (Praxis Educativa, 2025)
According to a qualitative narrative research approach, this work presents an initial interpretative analysis of the narratives of a teacher-research professor in the field of teacher education in the English Teacher Education Program of the National University of Mar del Plata. Taking as a source her own reflective narrative and an in-depth interview, the aim of this study is to explore how her knowledge and beliefs have evolved, from a dominant mode of existence to a decolonial perspective, and how this has influenced the formative practices of future generations of teachers in the context of teaching English otherwise. The narrative of our teacher educator reveals aspects of the unavoidable colonial influence in her own educational biography, indicates a gradual progression of her professional development and transformation, and highlights the decolonizing value of narrative research.